The Ability in Producing Acceptable Indonesian Translation of Comic Strip Made by Students of English Language Education Program of Universitas Negeri Padang - Riri Andria; Havid Ardi (Journal of English Language Teaching, 2021)
The aims of this research are to analyze the ability in producing acceptable Indonesian translation made by English Language Education students of Universitas Negeri Padang in translating English comic strip. This study was conducted by using descriptive research and using translation test as instrument collected from 36 students who have taken English-Indonesia Translation course in July-December 2020 of English Department, Universitas Negeri Padang. The sample in this research was chosen by using cluster random sampling. To get the trustworthiness of this research, this research applies the validator and three raters. The finding of this research showed that from 36 students, 17 (47.2 %) of them have excellent level of ability to produce acceptable translation, 18 students (50 %) have good level, and 1 student (2.8 %) has fairly good level of ability. In general students’ ability in producing acceptable Indonesian translation of comic strip is categorized as good level (79.9 %). Furthermore, the result of this research also showed that there are 17 students that produce acceptable translation, and 19 students that produce less acceptable translation in which the translation made by students sound still natural but there are inappropriate words or diction that are unfamiliar for the target readers.